Possible Involvement of p38 in Mechanisms Underlying Acceleration of Proliferation by 15-Deoxy-Δ12,14-prostaglandin J2 and the Precursors in Leukemia Cell Line THP-1 - Yasutaka Azuma; Kyoko Watanabe; Masataka Date; Michiharu Daito; Kiyoshi Ohura (Elsevier, 2004)
15-Deoxy-Δ12,14-prostaglandin J2 (15dPGJ2), which is a ligand for peroxisome proliferator-activated receptor γ (PPARγ), induced apoptosis of several human tumors including gastric, lung, colon, prostate, and breast. However, the role of PPARγ signals in other types of cancer cells (e.g., leukemia) except solid cancer cells is still unclear. The aim of this study is to evaluate the ability of 15dPGJ2 to modify the proliferation of the human leukemia cell line THP-1. 15dPGJ2 at 5 μM stimulated the proliferation in THP-1 at 24 to 72 h after incubation. In contrast, 15dPGJ2 at concentrations above 10 μM inhibited the proliferation through the induction of apoptosis. PGD2, PGJ2, and Δ12-PGJ2 (ΔPGJ2), precursors of 15dPGJ2, had similar proliferative effects at lower concentrations, whereas they induced apoptosis at high concentrations. 15dPGJ2 and three precursors failed to induce the differentiation in THP-1 as assessed by using the differentiation marker CD11b. FACScan analysis revealed that PGD2 at 5 μM, PGJ2 at 1 μM, ΔPGJ2 at 1 μM and 15dPGJ2 at 5 μM all accelerated cell cycle progression in THP-1. Immunoblotting analysis revealed that PGD2 at 5 μM and 15dPGJ2 at 5 μM inhibited the expression of phospho-p38, phospho-MKK3/MKK6, and phospho-ATF-2, and the expression of Cdk inhibitors including p18, p21, and p27 in THP-1. In contrast, PGJ2 at 1 μM and ΔPGJ2 at 1 μM did not affect their expressions. These results suggest that 15dPGJ2 and PGD2 may, through inactivation of the p38 mitogen-activated protein kinase pathway, inhibit the expression of Cdk inhibitors, leading to acceleration of the THP-1 proliferation. Keywords:: THP-1, proliferation, 15-deoxy-Δ12,14-prostaglandin J2, prostaglandin D2, p38